Urinary Tract Infection in Overactive Bladder: An Update on Pathophysiological Mechanisms - Mansfield, Kylie J.; Chen, Zhuoran; Moore, Kate H.; Grundy, Luke (Frontiers in Physiology, 2022)
Overactive bladder (OAB) is a clinical syndrome defined by urinary urgency, increased daytime urinary frequency and/or nocturia, with or without urinary incontinence, that affects approximately 11% of the western population. OAB is accepted as an idiopathic disorder, and is charactersied clinically in the absence of other organic diseases, including urinary tract infection. Despite this, a growing body of research provides evidence that a significant proportion of OAB patients have active bladder infection. This review discusses the key findings of recent laboratory and clinical studies, providing insight into the relationship between urinary tract infection, bladder inflammation, and the pathophysiology of OAB. We summarise an array of clinical studies that find OAB patients are significantly more likely than control patients to have pathogenic bacteria in their urine and increased bladder inflammation. This review reveals the complex nature of OAB, and highlights key laboratory studies that have begun to unravel how urinary tract infection and bladder inflammation can induce urinary urgency and urinary frequency. The evidence presented in this review supports the concept that urinary tract infection may be an underappreciated contributor to the pathophysiology of some OAB patients.